Forecasting with a forward-looking DGE model: combining long-run views of financial markes with macro forecasting - Hanna-Leena Männistö (Bank of Finland, 2005)
To develop forecasting procedures with a forward-looking dynamic general equilibrium model, we built a small New-Keynesian model and calibrated it to euro area data.It was essential in this context that we allowed for long-run growth in GDP.We brought additional asset price equations based on the expectations hypothesis and the Gordon growth model, into the standard open economy model, in order to extract information on private sector long-run expectations on fundamentals, and to combine that information into the macro economic forecast.We propose a method of transforming the model in forecasting use in such a way, as to match, in an economically meaningful way, the short-term forecast levels, especially of the model's jump-variables, to the parameters affecting the long-run trends of the key macroeconomic variables.More specifically, in the model we have used for illustrative purposes, we pinned down the long-run inflation expectations and domestic and foreign potential growth-rates using the model's steady state solution in combination with, by assumption, forward looking information in up-to-date financial market data.Consequently, our proposed solution preserves consistency with market expectations and results, as a favourable by-product, in forecast paths with no initial, first forecast period jumps.Furthermore, no ad hoc re-calibration is called for in the proposed forecasting procedures, which clearly is an advantage from point of view of transparency in communication.
URN:NBN:fi:bof-20140807324
Keywords: E17; E30; E31; F41; 330; forecasting; New Keynesian model; DSGE model; rational expectations; open economy